Myb genes from Hordeum vulgare : tissue‐specific expression of chimeric Myb promoter/ Gus genes in transgenic tobacco - Wissenbach, Margit; Überlacker, Bärbel; Vogt, Friederike; Becker, Dieter; Salamini, Francesco; Rohde, Wolfgang (The Plant journal : for cell and molecular biology, 1993)
The structures of the three Myb ‐related genes Hv1 , Hv5 and Hv33 from barley were determined. They contain a single intron located in the second repeat unit of the Myb ‐related domain. By analogy to the animal MYB oncoproteins this conserved region of the gene product was shown by filter‐binding experiments to exhibit nucleic acid‐binding activity. Tobacco plants transgenic for chimeric Myb promoter/ Gus genes express the enzyme in a developmentally controlled and tissue‐specific manner. During germination and early stages of plant growth, GUS activity is seen in the root cap and adjacent meristematic tissue. At later stages of plant development, GUS activity is predominantly observed in the shoot apical meristem, the roots and the nodal regions of the stem. Within the stem at stages of secondary growth, Myb promoters are active in defined cell types. In the internode low GUS activity is displayed by the innermost cell layer of the cortex, the starch sheath, that surrounds the vascular cylinder of secondary xylem and phloem tissue, as well as in pith rays originating from vascular cambium initials. In the nodal region Myb promoter‐controlled Gus expression is mainly confined to the abaxial starch sheath of the leaf trace, to the branch traces and to internal strands of primary phloem. It is suggested that in addition to their activity in meristematically active plant tissues Myb genes are expressed in conductive tissues that are closely associated with vascular bundles.